RESPON PETANI KARET THAILAND, INDONESIA, MALAYSIA, VIETNAM, INDIA, DAN LAOS MENGHADAPI RENDAHNYA HARGA KARET - Iif Rahmat Fauzi; Lindawati Lindawati (Jurnal Agro Estate, 2021)
In several years ago, the natural rubber price shows a negative trend. This condition make a rubber smallholder face difficulties in life. This paper study the efforts made by rubber smallholder to face low rubber prices. Methods in this paper used descriptive analysis with literature studies of the efforts undertaken by rubber smallholder in several rubber producer countries, especially in Thailand, Indonesia, Malaysia, Vietnam, India, and Laos to face low rubber price. This study show that the alternative effort undertaken by rubber smallholder to face low rubber price generally was 1) management of cost production by reduced fertilizer and others factor production which no disturbed rubber income; 2) develop other crops by intercropping technique on rubber interrow; 3) looking for side jobs such as construction laborers, public transportation drivers, opening stalls and catching fish; 4) take of loans to maintain the standard of household living; 5) implement a joint marketing system to obtain a better rubber price; 6 continue to tapping as usual and trying to access the government assistance programs that were oriented towards the sustainability of rubber agribusiness; 7) selling or renting out some of the old rubber land that is no longer productive; 8) carry out new plantings with or without government assistance. The alternative strategy that is considered the most relevant in dealing with low rubber prices and supporting the sustainability of natural rubber agribusiness at this time is the intercropping strategy